Thromboelastometric Analysis of the Correlation Between Burn-Induced Coagulopathy and Severity of Burn Injury - Koami, Hiroyuki; Sakamoto, Yuichiro; Matsuoka, Ayaka; Shinada, Kota (Cureus, 2024)
Background In this study, we aimed to analyze the association between the burn index (BI) and burn-induced coagulopathy. Methods Adult burn patients transported to our emergency department who underwent rotational thromboelastometry (ROTEM) between April 1, 2013, and December 31, 2021, were enrolled in this study. The patients were categorized into two groups based on burn severity. Severe burns were defined as BI scores of > 15. Patient demographics, clinical variables of burns, standard laboratory test data, ROTEM data, and clinical outcomes of both groups were evaluated. In addition, the correlation between severe burns and significant variables was evaluated using a univariate analysis. Results Seven patients were enrolled and categorized into the severe (n = 2) and control (n = 5) groups. The severe group had a significantly worse consciousness level and higher mortality rate and showed higher tendencies of burn severity and clinical severity scores. Disseminated intravascular coagulation was confirmed in one patient. All ROTEM variables in the severe group regarding clot firmness in the extrinsic coagulation cascade (EXTEM) and fibrinogen-specific coagulation cascade (FIBTEM) showed a decreasing tendency as compared to those in the control group. Moreover, correlation analyses revealed strong correlations between the BI and clot firmness (rho = -0.946 to -0.721). Conclusions Severe BI was strongly associated with decreased blood clot firmness in EXTEM, FIBTEM, and ROTEM. Future research using viscoelastic devices may provide new possibilities for the treatment of severe burns.